2020
DOI: 10.3390/nu12030776
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adherence to Specific Mediterranean Diet Components and Cardiorespiratory Fitness in Young Adults

Abstract: Objective: Cardiorespiratory fitness (CRF) and a healthy diet may be part of an overall healthy lifestyle. The association between cardiorespiratory fitness and adherence to an overall Mediterranean Diet (MedD) pattern and specific MedD foods has been assessed. Design: Subjects completed a lifestyle survey and dietary pattern, using the validated MedD Adherence 14-item questionnaire and two self-reported 24-h dietary recalls. Participants’ height, body weight, waist circumference (WC), and CRF (maximum oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
3
6
4
Order By: Relevance
“…The data obtained in the current study regarding physical activity after confinement indicated that most of the subjects practiced some degree of activity, exercising between two and three days a week. These data differ from the studies on physical activity carried out during quarantine, in which a great reduction in physical activity was observed in Spain; it was the European country with the highest rate of inactivity (close to 38%) as reported previously [26], since during the entire confinement there was no space provided at home to carry out exercise. This could lead to a loss of muscle mass and weight gain, which were factors associated with a worse prognosis in cases of SARS-CoV-2 infection by hindering the immune response to the disease [27].…”
Section: Discussioncontrasting
confidence: 99%
“…The data obtained in the current study regarding physical activity after confinement indicated that most of the subjects practiced some degree of activity, exercising between two and three days a week. These data differ from the studies on physical activity carried out during quarantine, in which a great reduction in physical activity was observed in Spain; it was the European country with the highest rate of inactivity (close to 38%) as reported previously [26], since during the entire confinement there was no space provided at home to carry out exercise. This could lead to a loss of muscle mass and weight gain, which were factors associated with a worse prognosis in cases of SARS-CoV-2 infection by hindering the immune response to the disease [27].…”
Section: Discussioncontrasting
confidence: 99%
“…It could be argued that Spain, a Mediterranean country, should have a higher adherence to the MedDiet. However, data from this study are consistent with those recently published by Santi-Cano et al [21] who reported a MedDiet average score of 6.2 ± 1.8 points in young adults, i.e., 275 university students from the South of Spain with mean age of 22.2 ± 6.3 years old. In fact, an abandonment by the MedDiet by the Spanish adults was earlier documented by León-Muñoz et al in 2012 [22].…”
Section: Discussionsupporting
confidence: 92%
“…These data are relevant if we compare them with those of the COVIDiet [7] study performed in an adult population during the confinement period in Spain. The scores of our student population were much higher than those observed in the COVIDiet study [15], where participants scored an average of 6.53 ± 2 points before the pandemic and 7.3 ± 1.93 points during home confinement between March and April 2020 [2]. One explanation for these differences between the two studies, as indicated in the DIMERICA study [16], may be that adherence to the MedDiet is affected by different aspects, such as place of residence and education level, and involves not only dietary patterns but also lifestyle, sociocultural, cultural heritage, and environmental aspects.…”
Section: Discussioncontrasting
confidence: 80%
“…We found an initial MedDiet adherence score of 9.03 ± 1.69 points among university students, indicating that participants had good dietary habits before the pandemic. Other similar studies examining the dietary habits of university students demonstrated lower or similar scores to those observed in the present study [8,14,15]; however, we did not find any studies demonstrating higher scores. These data are relevant if we compare them with those of the COVIDiet [7] study performed in an adult population during the confinement period in Spain.…”
Section: Discussionsupporting
confidence: 69%